ANALISIS STANDARD KOMPETENSI SEKRETARIS DI PT UNITED TRACTORS, TBK SURABAYA - Mustikawati, Farida (GEMA EKONOMI, 2012)
Developments currently in need of a secretary who not only handle the jobs that are familiar with the role of secretary, for example: correspondence, filing, travel arragement, etc.. These conditions make the company’s leaders need the services of a secretary who is more reliable and professional. Era of globalization and the advancement of science information technology demands of people - those who cultivate the professional secretary to always fit in and widen the horizons ability, not only the ability of correspondence, which must be mastered by the secretary. Level of competence which is now owned secretary needs to be improved so that in order to compete with the secretary of the personnel who are not unlikely to come from outside by foreign investors who have the opportunity to do business in Indonesia. Objectives to be achieved in this study was to determine the standard of competence secretary to become a professional secretary. Research used in this study was descriptive qualitative research is by using the method of observation to the company. The conclusion from the results of this study is that the secretary should know the scope of work and standard of competence is needed for a secretary so the secretary can become a competent professional secretary in his field.